Olefin polymerization catalyst based on organometallic complexes and processes for production of polyolefins using the catalyst - SATO, MORIHIKO; HAMURA, SATOSHI; YOSHIDA, TORU (1997)
A novel class of olefin polymerization catalyst systems based on specific organo-transition metal compounds and which are effective for controlling in particular the width and mode of the molecular weight distribution of the resulting polyolefins, and processes of olefin polymerization using the novel catalyst systems are disclosed.